DNA methylation of PTGER4 in peripheral blood plasma helps to distinguish between lung cancer, benign pulmonary nodules and chronic obstructive pulmonary disease patients. (April 2021) - Schotten, Lea M.; Darwiche, Kaid; Seweryn, Michal; Yildiz, Vedat; Kneuertz, Peter J.; Eberhardt, Wilfried E.E.; Eisenmann, Stephan; Welter, Stefan; Sisson, Brianna E.; Pietrzak, Maciej; Wiesweg, Marcel; Ploenes, Till; et al.
Abstract: Background/introduction: In contrast to patients who present with advanced stage lung cancer and associated poor prognosis, patients with early-stage lung cancer may be candidates for curative treatments. The results of the NELSON lung cancer screening trial are expected to stimulate the development and implementation of a lung cancer screening strategy in most countries. Widespread use of chest computed tomography scans will also result in the detection of solitary pulmonary nodules. Because reliable biomarkers to distinguish between malignant and benign lesions are lacking, tissue-based histopathological diagnostics remain the gold standard. In this study, we aimed to establish a test to assess the predictive ability of DNA hypermethylation of SHOX2 and PTGER4 in plasma to discriminate between patients with 1.) lung cancer, 2.) benign lesions, and 3.) patients with chronic obstructive pulmonary disease (COPD). Patients and methods: We retrospectively analysed SHOX2 and PTGER4 methylation in 121 prospectively collected plasma samples of patients with lung cancer (group 1A), benign lesions (group 1B), and COPD without nodules (group 2). Results: PTGER4 DNA hypermethylation was more frequently observed in patients with lung cancer than in controls (p = 0.0004). Results remained significant after correction for tumour volume, smoking status, age, and eligibility for the NELSON trial. Conclusions: Detection of methylated PTGER4 in plasma DNA may serve as a biomarker to support clinical decision-making in patients with pulmonary lesions at lung cancer screening in high-risk populations. Further exploration in prospective studies is warranted. Highlights: mPTGER4 and mSHOX2 were assessed to improve lung cancer diagnostics. Lung cancer was compared with benign pulmonary nodules and COPD. Hypermethylation of PTGER4 helps to distinguish patients with lung cancer from controls.